The benefit of artificial oocyte activation is dependent on the fertilization rate in a previous treatment cycle - Montag, Markus (Reproductive biomedicine online, 2012)
Following intracytoplasmic sperm injection (ICSI), some patients present low or zero fertilization rates. Artificial oocyte activation has been proposed as a suitable means to overcome this problem. This study applied artificial oocyte activation in patient cohorts with a history of no fertilization (0%, group 1), fertilization between 1 and 29% (group 2) or fertilization between 30 and 50% (group 3) in initial ICSI cycles. In the following treatment cycles, oocytes were activated after ICSI using calcium ionophore. Fertilization, pregnancy and take-home baby rates were compared with the previous cycle without activation. In group 1, fertilization rate was 41.6%, embryos for transfer were available in 82.1% of cycles, giving a clinical pregnancy rate of 18.8% and take-home baby rate of 12.8%. In group 2, despite a lower transfer rate (87.9% versus 100%, P<0.05), there were higher fertilization and clinical pregnancy rates (44.4% versus 19.3% and 31.4% versus 12.8%, respectively, P<0.05) and take-home baby rate was 24.1% versus 12.8%. In group 3, fertilization rates differed (56.1% versus 36.8%; P<0.001) but all other parameters were similar. Artificial oocyte activation has great potential especially in patients showing compromised fertilization rates below 30% after standard ICSI. Following intracytoplasmic sperm injection (ICSI), some patients present very low or even zero fertilization rates after ICSI. Artificial oocyte activation has been proposed as a suitable means to overcome this problem. We applied artificial oocyte activation in patients which presented a history either no fertilization, fertilization between 0 and 30% or fertilization between 30 and 50% in initial ICSI cycles. In the following treatment cycles, oocytes were activated after ICSI using a calcium ionophore. Fertilization, pregnancy and take-home baby rates were compared to the previous cycle without activation. For the groups with previously 0% or 1-29% fertilization, we noted higher fertilization rates and clinical pregnancy rates per embryo transfer. For the group with moderate fertilization, only fertilization rates differed but all other parameters were not significantly different. From these data we conclude that artificial oocyte activation has a great potential especially in patients which show a compromised fertilization rate below 30% in a standard ICSI cycle.
Gesehen am 26.04.2018